1999
DOI: 10.1111/j.1346-8138.1999.tb02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo: Clinical Findings in 1436 Patients

Abstract: We retrospectively analyzed the clinical and epidemiological profiles of patients with vitiligo attending the pigmentary dermatoses clinic. One thousand four hundred and thirty-six patients were seen between 1989 and 1993. Males constituted 54.5% of the group and females 45.5%. Mean age of the patients was 25 years, and average disease duration at the time of hospital visit was 3.7 years. Vitiligo vulgaris was the commonest form of the disease in 1002 (69.8%) patients followed by focal vitiligo in 214 (14.9%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
160
19
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(216 citation statements)
references
References 10 publications
31
160
19
6
Order By: Relevance
“…18 High frequency of thyroid dysfunctions have been reported among vitiligo patients than in the normal controls. [18][19][20][21] In this study, 26.7% of the vitiligo patients were observed to have various degrees of thyroid dysfunctions which is in accord with the finding by Jishna et al, who reported an incidence rate of 27% of thyroid dysfunctions among vitiligo patients but at variance with the findings of Altraide et al in a retrospective study reported from Nigeria in 2009. 22,4 Altraide et al had reported a 9.8% frequency of thyroid dysfunctions among vitiligo subjects in their study.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…18 High frequency of thyroid dysfunctions have been reported among vitiligo patients than in the normal controls. [18][19][20][21] In this study, 26.7% of the vitiligo patients were observed to have various degrees of thyroid dysfunctions which is in accord with the finding by Jishna et al, who reported an incidence rate of 27% of thyroid dysfunctions among vitiligo patients but at variance with the findings of Altraide et al in a retrospective study reported from Nigeria in 2009. 22,4 Altraide et al had reported a 9.8% frequency of thyroid dysfunctions among vitiligo subjects in their study.…”
Section: Discussioncontrasting
confidence: 44%
“…5 This is evidenced by its familial propensities, histological proof of cytotoxic inflammatory cells in vitiligo lesions, its response to immunosuppressive agents and its frequent association with various autoantibodies and coexistence with other autoimmune disorders. [18][19][20][21] The theory of autoimmunity in etio-pathogenesis of vitiligo proposes alteration in both humoral and cellular immunity leading to the destruction of melanocytes and simultaneous involvement of various other organ-specific tissues. 18 High frequency of thyroid dysfunctions have been reported among vitiligo patients than in the normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…V itiligo is an acquired and highly stigmatizing disease that affects between 1 and 2% of the worldwide population (1)(2)(3). It is characterized by variable numbers of depigmented macules, which are often symmetrically placed and frequently affect exposed body areas and the skin around orifices (1,2).…”
mentioning
confidence: 99%
“…The disease distibitution for vitiligo was almost same in both genders (male: female 43.67%: 56.3%). Various studies have shown the disease distribution to be same in both sexes 11,12,13 , though a few studies have documented a higher incidence in females as was seen by Shah et al 10 and who attributed it to early seeking of medical attention by females in view of cosmetic reasons. We saw that vitiligo was most common in the young age group of 10 to 30 years.…”
Section: Discussionmentioning
confidence: 91%